Uji efek Hipnotik sedatif ekstrak etanol Batang Jaka Tua (Scoparia dulcis Linn) terhadap Mencit Jantan Galur Swiss - Gilbert Lister (Universitas Adiwangsa Jambi, 2024)
This study aims to evaluate the hypnotic and sedative effects of ethanol extract from the stem of Jaka Tua (Scoparia dulcis Linn) on male Swiss strain mice. The sleep time method with sodium pentobarbital induction was used to assess the extract’s potential to enhance sleep duration. The experiment was conducted at the laboratory of Universitas Adiwangsa Jambi. Mice were divided into five treatment groups: a negative control group (distilled water), a positive control group (diazepam 1 mg/kgBW), and three groups receiving the ethanol extract of Scoparia dulcis stems at doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW. Observed parameters included sleep onset time and total sleep duration. Results showed that administration of the extract at 200 mg/kgBW and 400 mg/kgBW significantly increased sleep duration and decreased sleep onset time compared to the negative control. The sedative effect at the highest dose approached that of diazepam. These findings suggest that the stem extract of Scoparia dulcis Linn possesses potential as a natural sedative agent.